2019
DOI: 10.3390/ijms20051060
|View full text |Cite
|
Sign up to set email alerts
|

Histone Acetylation of Immune Regulatory Genes in Human Placenta in Association with Maternal Intake of Olive Oil and Fish Consumption

Abstract: Maternal diet modifies epigenetic programming in offspring, a potentially critical factor in the immune dysregulation of modern societies. We previously found that prenatal fish oil supplementation affects neonatal T-cell histone acetylation of genes implicated in adaptive immunity including PRKCZ, IL13, and TBX21. In this study, we measured H3 and H4 histone acetylation levels by chromatin immunoprecipitation in 173 term placentas collected in the prospective birth cohort, ALADDIN, in which information on lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…Fatty acids in asthma can affect the equilibrium between pro- and anti-inflammatory mechanisms: n-3 polyunsaturated fatty acids (PUFAs) or monounsaturated fatty acids (MUFAs) could reduce inflammation, while saturated fatty acids (SFAs) may contribute to proinflammatory responses [ 29 ]. PUFAs seem also to be associated with a lower risk of allergic disease development in early childhood years, playing a protective role against allergy development [ 30 , 31 ]. Furthermore, as suggested by our data, also a previous study did not show correlations between fatty acid profile and ICS treatment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids in asthma can affect the equilibrium between pro- and anti-inflammatory mechanisms: n-3 polyunsaturated fatty acids (PUFAs) or monounsaturated fatty acids (MUFAs) could reduce inflammation, while saturated fatty acids (SFAs) may contribute to proinflammatory responses [ 29 ]. PUFAs seem also to be associated with a lower risk of allergic disease development in early childhood years, playing a protective role against allergy development [ 30 , 31 ]. Furthermore, as suggested by our data, also a previous study did not show correlations between fatty acid profile and ICS treatment [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, also epigenetic modifications mentioned above represent an interplay between genes and the environment as these heritable changes in gene function might be modified by environmental factors, such as diet, PA, or smoking, which was shown for T2D, 36,37 obesity, 37 and other chronic immunometabolic diseases. 38,39 It is generally known that PA protects against T2D, but it is still a matter of debate whether the effectiveness of exercise is dependent on the genetic background of patients, especially in terms of T2D development. The Diabetes Prevention Program 40 -one of the largest intervention studies in T2D development-has shown that there is no significant interaction between the treatment group and the genetic risk, expressed as GRS of T2D loci.…”
Section: Association Between Family History Level Of Physical Activimentioning
confidence: 99%
“…A few studies have investigated the direct role of histone modifications in allergic disorders other than CMA. These studies clearly demonstrate the importance of this type of epigenetic modification in etiology and pathophysiology of allergies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Whereas most of these studies investigated histone modification of genes involved in asthma, Harb et al explored the acetylation status of several genes in the placenta and correlated these with the prevalence of sensitization in children [ 28 ].…”
Section: Introductionmentioning
confidence: 80%